Angiogenesis of brain after ischemia/reperfusion injury of brain in aged rats and changes in expressions of basic fibroblast growth factor and transformation growth factor-β1 - Li, Jian-Sheng (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2010)
OBJECTIVE: To elucidate the mechanism of angiogenesis after cerebral ischemia/reperfusion (I/R) in the aged rats by observing the changes in expressions of basic fibroblast growth factor (bFGF) and transformation growth factor-β1 (TGF-β1)